Has Australia backdated the Human Revolution? - Stringer, Chris
Australia has usually played a supporting role in the story of human evolution Ñ regarded as a place at the edge of the inhabited world where modern humans arrived relatively late and then remained largely isolated from subsequent developments. However, new dates for a human burial at Mungo, New South Wales (Thorne et al. 1999) may not only force revision of views about the peopling of Australia, but also have a wider impact on ideas about modern human origins.